Keith Haring : on Park Avenue : An exhibition of the Public Art Fund - Galloway, David; André Emmerich Gallery, New York (New York : André Emmerich Gallery New York, 1997)
Installation of 14 sculptures on the Park Avenue Malls between 53rd and 74th Streets and Doris C. Freedman Plaza, New York City,1997-06-16 till 1997-10-10
biog., coll., ind. tent. p. 18
Keith Haring : Keith Haring on Park Avenue, André Emmerich Gallery, New York, June 16 - October 10 1997
Engels
boek
Keywords: Haring, Keith